Effect of rotation speed on microstructure and properties of dissimilar submerged friction stir welding joints of aluminium and pure copper - WANG Ying-hui; WANG Kuai-she; WANG Wen; PENG Pai; CHE Qian-ying; QIAO Ke (Cailiao gongcheng, 2019)
2024-T4 aluminium alloy and pure copper were welded by submerged friction stir welding (SFSW) and the effect of rotation speed on microstructure and mechanical properties of SFSW joints was studied. The results indicate that the SFSW joint is well formed, without cracks, holes and other defects. With the increase of rotation speed, the surface of the SFSW joint is smooth and the smoothness is improved. Meanwhile a large number of copper is involved in the nugget zone (NZ), and the structure in NZ is gradually disordered; the forced cooling effect of water effectively inhibits the formation of grain coarsening and brittle intermetallic compound during SFSW; the tensile strength of joint is 227MPa, which is 70.3% of the tensile strength of the copper base metal(BM) at the rotational speed of 750r/min and the tensile strength and elongation of the SFSW joint decrease with the increase of rotation speed.